Luis de Molina on iura peregrinandi, degendi ac comercii and the French presence in Brazil”, in M. Kaufmann, C. Haar, C. Müller (eds.), Civilisation, Nature, Subjugation. Variations of (De-)Colonization, Frankfurt, P. Lang Verlag, 19-33. - Teixeira, Cláudia (2021)
addresses the commentaries made by Luis de Molina in 1574 and 1593 on the title of naturalis societatis et communicationis (Francisco de Vitoria, De Indis recenter inventis relectio prior), arguing that the limitations Molina imposes on the iura peregrinandi, degendi ac comercii (rights to travel, dwell and trade) may have been influenced by the French attempt to establish a colony in Brazil, threatening the hegemonic control of the Portuguese Crown over the region. In this sense, the limitations imposed by Molina on these rights constitutes a sign of the paradigmatic shift that will occur from the end of the century onwards, conditioned by the emergence of competing powers who claimed access to the overseas territories and threatened the world-order established by the Tordesillas Treaty.